Radical Reactions in Organic Synthesis: Exploring in-, on-, and with-Water Methods - Chatgiglialoglu, Chryssostomos (2024)
Radical reactions in water or aqueous media are important for organic synthesis, realizing high-yielding processes under non-toxic and environmentally friendly conditions. This overview includes (i) a general introduction to organic chemistry in water and aqueous media, (ii) synthetic approaches in, on, and with water as well as in heterogeneous phases, (iii) reactions of carbon-centered radicals with water (or deuterium oxide) activated through coordination with various Lewis acids, (iv) photocatalysis in water and aqueous media, and (v) synthetic applications bioinspired by naturally occurring processes. A wide range of chemical processes and synthetic strategies under different experimental conditions have been reviewed that lead to important functional group translocation and transformation reactions, leading to the preparation of complex molecules. These results reveal how water as a solvent/medium/reagent in radical chemistry has matured over the last two decades, with further discoveries anticipated in the near future.